2016
DOI: 10.21873/anticanres.11095
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Expression Regulates Cell Migration of Human Colonic Adenocarcinoma Cells Through Gelsolin

Abstract: β-Catenin seems to be involved in the regulation of gelsolin expression, which in turn affects the migratory ability of colonic cancer cells. Our results could have important implications for the design of new anticancer therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…β-Catenin acts a pivotal part in wound repair of the skin, and it has been confirmed to regulate cell motility and adhesion. Several studies have been reported that β-catenin translocation into the nucleus accelerates cell metastasis and promotes both the secretion of TGFβ1 and the activation of MMP expression [3436]. TGFβ1 is a group of multifunctional growth factor that acts important impacts on wound healing by regulating the capacities of cell migration and proliferation, ECM production and remodeling, and immune response.…”
Section: Discussionmentioning
confidence: 99%
“…β-Catenin acts a pivotal part in wound repair of the skin, and it has been confirmed to regulate cell motility and adhesion. Several studies have been reported that β-catenin translocation into the nucleus accelerates cell metastasis and promotes both the secretion of TGFβ1 and the activation of MMP expression [3436]. TGFβ1 is a group of multifunctional growth factor that acts important impacts on wound healing by regulating the capacities of cell migration and proliferation, ECM production and remodeling, and immune response.…”
Section: Discussionmentioning
confidence: 99%
“…While the WNT/ β-catenin signal can be activated when WNT-seven-pass transmembrane Frizzled (Fz)-low-density lipoprotein receptor-related protein 6 complex is formed to inhibit the AXIN complex to degrade β-catenin, all of these will lead to the β-catenin stabilization, accumulation, and translocation to the nuclear to partner with T-cell factor (TCF) to activate WNT targeting gene expression. [21][22][23] All of these indicate that cytosolic CTNNB1 degradation by the APC/Axin1 destruction complex represents a key step in the Wnt pathway. 24,25 It is worth noting that the aberrant activation of Wnt/β-catenin and its interaction with TCF will further transcribe some oncogenes expression in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate the cell sheet “tissue effect” [ 21 ] and impact of centrifugation, relative gene expression of cell–cell and cell–matrix interaction proteins was compared among single cell suspension, conventional, and centrifuged one-layer sheets 24 h after fabrication. Gene expression for β-catenin, that intracellularly binds extracellular cadherin to mediate cell adhesion between adjacent cells [ 45 , 46 ], was significantly decreased by centrifugation relative to conventional cell sheets ( p = 0.023), though conventional sheet fabrication alone significantly upregulated β-catenin relative to the single cell control ( Figure 4 a). Gene expression for connexin 43, a cross-membranal gap junction protein that forms between physically adjacent cells and facilitates direct intracellular molecular signaling exchange [ 47 ], was significantly upregulated in centrifuged cell sheets relative to conventional cell sheets ( p = 0.020) and single cells ( Figure 4 b).…”
Section: Resultsmentioning
confidence: 99%
“…Cell shape change, regulated by the actin cytoskeleton [ 54 ], did not appear to be a major contributing factor in centrifuged tissue compaction ( Figure 3 i). β-catenin regulates cadherin-mediated cell adhesion and the migratory ability of cells [ 45 , 46 ]; the measured decrease in centrifuged sheet β-catenin gene expression further evidence inhibited cell migratory potential in the tight-packed tissue structure with high intercellular adhesive tension ( Figure 4 a). Importantly, gene expression for proteins that mediate the biochemical interaction of neighboring cells, namely connexin 43, a cross-membranal gap junction protein [ 47 ], integrin β1, an extracellular ECM binding protein [ 48 ], and laminin α5, an integrin-receptor ligand [ 49 ], were significantly upregulated due to one-layer sheet centrifugation ( Figure 4 b–d).…”
Section: Discussionmentioning
confidence: 99%